2019
DOI: 10.1002/zaac.201900048
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized Functional MOFs Loading Ag/AgBr with Throughout‐Visible‐Light Absorption for High‐Efficiency Photocatalysis

Abstract: Porous metal‐organic frameworks (MOFs) loading metal nanoparticles to form a composite photocatalyst demonstrated unique advantages. Modification of the electron donating group on the aromatic linkers of MOFs could increase the absorption range of light, thereby increasing the photocatalytic activity. In this study, we prepared a composite photocatalyst using a stable NH2‐functionalized MOF (UiO‐66‐NH2) to load semiconductor Ag/AgBr nanoparticles, and the resultant composites have intense optical absorption th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Metal organic frameworks (MOFs) are a new member of the porous material family and have been greatly attracted due to its adjustable pore size, large specific surface area and abundant organic functional groups, having potential applications in supercapacitors, lithium‐ion batteries, catalysts, sensors, medicine and so on. Many studies have demonstrated that medium strength MOFs can be readily obtained using polycarboxylic acids as monodentate, bidentate or multidentate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Metal organic frameworks (MOFs) are a new member of the porous material family and have been greatly attracted due to its adjustable pore size, large specific surface area and abundant organic functional groups, having potential applications in supercapacitors, lithium‐ion batteries, catalysts, sensors, medicine and so on. Many studies have demonstrated that medium strength MOFs can be readily obtained using polycarboxylic acids as monodentate, bidentate or multidentate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…MOF material is a kind of porous material attracting much attention in recent years. Because of its high specific surface area and porosity, MOFs have been used in fields like gas adsorption, [11,12] catalysis, [13,14,15] solid electrolyte or interlayer in batteries. [16,17,18] The high specific surface area and porosity grant MOFs material the potential to be used as the carrier material of chemical heat pump solid adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Metal-organic frameworks (MOFs) [12][13] are crystalline materials with ordered pore structures formed by the coordination self-assembly [14][15] of metal ions and organic ligands. MOFs had the advantages of large specific surface area, [16] high porosity [17] and large pore volume, [18] which made it attracted extensive attention in sensing, [19][20][21][22][23] separation, [24] catalysis, [25] gas storage [26] and drug carrier. [27] Especially in the biomedical field, the diverse components [28] and modifiability [29] of material could encapsulated a variety of therapeutic agents to achieve multimodal therapy.…”
Section: Introductionmentioning
confidence: 99%